Benefits of omalizumab on anxiety and depression in patients with severe asthma - Fatih Uzer (Caspian Journal of Internal Medicine, 2018)
Background: Asthma is one of the most common chronic diseases and may cause psychiatric disorders affecting the patients’ quality of life. In our study, we evaluated the effect of omalizumab treatment on anxiety disorder and depression using Beck Depression Scale (BDS) and State Trait Anxiety Inventory (STAI). Methods: Anxiety level was determined with STAI, whereas depression level was evaluated by BDS. Patients were asked to mark the questionnaires to reflect their emotional state before treatment, and to reflect their emotions they are feeding in the current moment. All patients receiving omalizumab treatment were included in the study. Patients with known neuropsychiatric disorder were excluded from the study. Results: A total of 20 patients with mean age of 50.25 years were enrolled in the study. Gender distribution was: 5(25%) male patients and 15(75%) female patients.  All patients with severe asthma received omalizumab treatment. The omalizumab treatment period was shown for mean 17.6 months (2-40 months). In anxiety scales, there was statistically significant difference compared with pretreatment and posttreatment periods. Depression (moderate to severe) was present in 12 patients before omalizumab treatment and 3 patients after omalizumab treatment. Conclusions: Uncontrolled asthma as a chronic disorder can cause depressive symptoms and worsen quality of life. We believe by controlling asthma, quality of life will improvein such patients. In appropriate indication, omalizumab can improve depression and anxiety in asthma patients.